2009
DOI: 10.1186/1758-3284-1-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single versus fractionated dose of stereotactic radiotherapy for salvaging local failures of nasopharyngeal carcinoma: a matched-cohort analysis

Abstract: Background: wLocal failure is an important cause of morbidity and mortality in nasopharyngeal carcinoma (NPC). Although surgery or brachytherapy may be feasible in selected cases, most patients with local failure require external beam re-irradiation. Stereotactic radiation using single or multiple fractions have been employed in re-irradiation of NPC, but the optimal fractionation scheme and dose are not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…In patient with local failure of nasopharyngeal cancer, Chua et al reported that incidence of severe late complications was 33% in SRS group vs. 21% in hSRT group, including brain necrosis (16% vs. 12%) and hemorrhage (5% vs. 2%) and they preferred use of fractionated treatment [15]. Cengiz et al reported a high incidence (15%) of bleeding after hSRT using the CyberKnife system [11]; this value was similar to that (9.5%) reported by us in a previous study [10].…”
Section: Discussionmentioning
confidence: 96%
“…In patient with local failure of nasopharyngeal cancer, Chua et al reported that incidence of severe late complications was 33% in SRS group vs. 21% in hSRT group, including brain necrosis (16% vs. 12%) and hemorrhage (5% vs. 2%) and they preferred use of fractionated treatment [15]. Cengiz et al reported a high incidence (15%) of bleeding after hSRT using the CyberKnife system [11]; this value was similar to that (9.5%) reported by us in a previous study [10].…”
Section: Discussionmentioning
confidence: 96%
“…Assuming an α/β ratio of 3 Gy and estimating that a bed-σ (summated bed) of 143 Gy would induce 20% more toxicity than a bed-1 (primary course) of 111 Gy, they found that 58 found that a total equivalent dose of 50 Gy or more improved local control. A study by Chua et al 48 compared single-fraction (srs) and multiple-fraction (srm) stereotactic radiotherapy in a matched-pair design. Compared with srs, srm led to better local control in npc (p = 0.003), but os was not significantly different (p = 0.31).…”
Section: What Is the Optimal Dose And Fractionation When Delivering Rmentioning
confidence: 99%
“…Chua and Wu et al compared their treatment results in a matched cohort analysis [29]. Patients were matched individually for the following prognostic factors: persistent versus recurrent disease, rT stage, and tumor volume.…”
Section: Treatmentmentioning
confidence: 99%